CHARACTERISTICS OF WATER USE AND VOLUME OF WASTEWATER DISCHARGE IN THE SURFACE WATER OF THE INDUSTRIAL REGION - Вальчук, Сергей; Рублевская, Надежда; Коваль, Вадим; Похмурко, Инна (SWorldJournal, 2021)
The article describes the volume of industrial wastewater discharges into the surface reservoirs of Dnipropetrovsk region in the dynamics of 2015-2019. 1.36 times the amount of discharge of return water into the surface water body in 2019, due to the decl